Effect of The Addition of Acacia Powder Ash and Carbide Welding Ash to Increase the Production of Brick Craftsmen - Marlia Adriana; Norminawati Dewi; Budi Kurniawan; Intan Safitri (International Journal of Research in Vocational Studies (IJRVOCAS), 2023)
Many bricks are produced by small business and industries as construction materials. As the population increases, there is also more demand for bricks in construction construction. The materials used in this study are waste from the acacia wood burning process and carbide welding ash waste. These two materials will be tested into additives from making bricks. The research method was carried out using testing of moisture content, specific gravity, Atterberg limit testing (Liquid limit) as well as a visual description of bricks with an outside temperature without a combustion process. Of the three samples, the average moisture content obtained, the lowest moisture content value was 69.41% in a mixture of clay soil plus acacia ash which showed that the soil category was a soft organic clay category with the characteristic that the soil could be pressed with the tip of the thumb so that the soil was suitable to be used as additional raw material in making stone stones without burning. The results of the average soil specific gravity test of 2 samples showed a Gs value of 2.64 at a temperature of t0 C, this shows that the soil with the organic clay category is in accordance with the test results on the moisture content that the clay soil is the basic raw material. The liquid limit test in this study showed the average value of water content in bricks without additives as much as 120.36%: the average value of water content in bricks with additives from the values of the three samples can be known that the mineral clay material is of the montmorillonite type with a liquid limit value of 100-900. Visual observations showed that bricks printed using clay soil raw materials without additives showed a break (split) in half during the drying process for 2 days with a temperature of 30oC; the mixture of clay soil and welded ash of the brick carbide experienced small cracks / crak on the surface with the drying process at the same temperature while the mixture of clay soil with acacia ash showed intact bricks without intact bricks without fractures or cracks on the surface in the drying process using the same temperature.